Numerical study of heat transfer influence on the performance of a single screw expander for Organic Rankine Cycle. (15th February 2020) - Wang, Wei; Shen, Li-li; Chen, Ru-meng; Wu, Yu-ting; Ma, Chong-fang
Abstract: Heat dissipation was the one of the irreversible losses of expanders. For small capacity expanders, the influence of it on the performance of expanders might be more significant. Single screw expander (SSE) was a type of volumetric expander, which has a certain advantages in the Organic Rankine Cycle system. Investigating the characteristics of heat transfer in SSE was necessary because of the influence on the performance. This study discussed the effect of heat transfer on thermodynamic performance for a SSE. Combined leakage and heat transfer, the thermodynamic model of working process was established firstly. Lubricating oil heat absorption was considered in heat transfer model. For heat transfer in the body, it was divided into 17 parts and calculated the temperature distribution by lumped parameter method. The coupling model was computational programmed by the method of multiple separate solutions. Then, experimental study on heat dissipation of SSE for Organic Rankine Cycle was carried out and verified the model. R123 was selected as working fluid. Finally, the influence of heat transfer on the performance of the SSE was analyzed from different influence factors. From the simulation results, the range of heat transfer influence for the power was from 1.91% to 4.51%, and that for the efficiency was from 2.72% to 5.78%, under the different working conditions. Moreover, the effect of heat transfer on performance at low inlet pressure was greater than that at high inlet pressure. It can also be seen that the effect of heat transfer on the efficiency was greater than that on the power. Therefore, it could be concluded that the effect of heat transfer on the performance of SSEs was relatively small. Highlights: The heat transfer for SSE body was simulated by lumped parameter method. The performance for SSE was simulated by coupled numerical model. The simulation results had a good agreement with the experiment results. The heat transfer influence for power was 1.91%–4.51% in the set conditions. The heat transfer influence for efficiency was 2.72%–5.78% in the set conditions.